Tratamiento antitrombótico en pacientes con prótesis valvular cardíaca. Antithrombotic therapy in patients with prosthetic heart valves. - Fidel Manuel Cáceres Lóriga; Horacio Pérez López; Karel Morlans Hernández (ECIMED, 2000)
Los episodios tromboembólicos continúan siendo una complicación importante en los pacientes con sustitución de alguna de las válvulas cardíacas a pesar de los avances en el diseño de las prótesis. Al revisar la literatura, comprobamos que las modalidades de anticoagulación menos intensa, con tratamiento antiagregante plaquetario o sin él, han sido eficaces y seguras en estos enfermos. La anticoagulación recomendada por vía oral para prótesis biológicas debe alcanzar una razón normalizada internacional de 2,0 a 3,0 y de menor intensidad que la administrada anteriormente para los pacientes con prótesis mecánicas. The thromboembolic events are still an important complication in patients with substitution of any of the heart valves in spite of the advances obtained in the design of prostheses. On reviewing literature, we confirm that the modalities of less intense anticoagulation, with platelet antiaggregant treatment or without it , have been efficient and safe in these patients. The recommended oral anticoagulation therapy for biological protheses should attain an international standardized range from 2,0 to 3,0 and of lower intensity than that previously administered to patients with mechanical prostheses.